The Relationship Between The Polymorphism of Beta A (Βa) Sheet of Inhibin Gene and Semen Characteristics in Holstein Bulls - Qusay Mohammed Aboud; Laith Sofian Younis (مجلة الانبار للعلوم البيطرية)
This study aimed to test a linkage between Inhibin beta A (INHβA) polymorphism and semen quality in Holstein bulls in Iraqi Artificial Insemination Center. The experiment trial was carried out on (12 n) pure Holstein breed bulls. The study period started from January 2022 until February 2022. The Ejaculates were collected and its characteristics were evaluated immediately, additionally, 10 ml of blood were collected from each bull (12 samples) for genomic DNA extraction to determine the single nucleotide polymorphisms (SNPs) and compared with semen quality. The findings showed the presence of four variants at Exon 2; C (903) T, C (916)Y, G (917)K, and G (966) R in Exon 2 when compared with Gene sequence ID: XM_024990466.1. Two out of four Exon 2 SNPs were non-sense mutations(C (903) T and G (966) R), while the remains were missense which made the change in Arginine > phenylalanine at position (306). Regarding the volume of ejaculates, the results recorded that non-significant difference was shown in whole alleles of the loci, except in one locus (G (966) R), the bulls that had a wild allele (A) recorded maximum collected volume (p < 0.001). In addition, the bulls that represented wild genotypes showed a significant increase in sperm concentration and both mass and individual motility than mutant genotypes in all loci. Moreover, The results of the dead sperm percentage showed a non-significant correlation between the genotypes of all loci except in C (903) T, which demonstrated the superiority of the wild allele over the mutant. Lastly, the results prevailed that the mutant genotype related to the bad semen quality for the bulls, while, the wild genotypes showed good semen parameters, these results may be due to the effect of SNPs on the expression of INHA or the increase in its activity.